Connectionism’s new wave. Reexamining two theories of machine consciousness. - CHIRILĂ, Alexandra (Annals of Philosophy, Social & Human Disciplines, 2025)
This paper analyses the possibility of machine consciousness concerning Daniel C. Dennett and John R. Searle, in the light of the most recent technological advancements. We will consider the opposing views that each author has of qualia and how it either widens or narrows the possibility of machine consciousness. While Dennett strongly believes that human-like artificial intelligence is just a matter of time, Searle thinks that until we solve the problem of how the mind works, the idea of an AI that does everything humans are capable of is far from reality. Dennett reinforces his beliefs about this kind of AI, based on the concept of strange inversion of reason. On the other hand, Searle states that consciousness can be causally reduced to neural activity, but not ontologically. Even though connectionism used to be popular two decades ago, recent developments in Deep Learning have made connectionism return to the spotlight, with software like AlphaZero, Chat GPT, and DALLE. Artificial neural networks are becoming more complex and nuanced, and this calls for a revisit of the classic arguments mentioned above to determine their relevance in light of the most recent developments. This paper aims to determine whether any of these views can still help researchers and engineers when considering state-of-the-art technologies and future developments in AI.